1958
DOI: 10.1029/tr039i004p00648
|View full text |Cite
|
Sign up to set email alerts
|

The effects of entrapped gases on the hydraulic characteristics of porous media

Abstract: Investigation of the hydraulic characteristics of prepared porous media indicate that a ten per cent increase in air content of media voids is capable of producing a 15 pct reduction in ‘effective porosity,’ a 35 pct decrease in permeability, and about 50 pct reduction in hydraulic dispersion. The location of bubbles in large or small pores affects the uniformity of pore sizes and determines the amount of water saturated void volume which is isolated by air bubbles. The shape of the chloride tracer ‘breakthrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 3 publications
3
32
0
Order By: Relevance
“…The long-column test results were similar to other studies with respect to changes in saturated hydraulic conductivity with intermittent wetting (Orlob and Radhakrishna 1958;Samani 1983;Jalali-Farhani et al 1993b). Average in®ltration rates and saturated hydraulic conductivity for all long-column tests decreased from the ®rst wetting to the second.…”
Section: Long-column Testssupporting
confidence: 78%
See 1 more Smart Citation
“…The long-column test results were similar to other studies with respect to changes in saturated hydraulic conductivity with intermittent wetting (Orlob and Radhakrishna 1958;Samani 1983;Jalali-Farhani et al 1993b). Average in®ltration rates and saturated hydraulic conductivity for all long-column tests decreased from the ®rst wetting to the second.…”
Section: Long-column Testssupporting
confidence: 78%
“…Izadi et al (1995) demonstrated through computer modeling that entrapped air could signi®cantly decrease in®ltration rates. Orlob and Radhakrishna (1958) found signi®cant eects on permeability from varying degrees of air entrapment of saturated soil columns.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that gas may be introduced during the injection phase. Orlob and Radhakrishna found that in an inhomogenous medium, there will be less dispersion if gas bubbles were entrapped in the larger pores, but no effect on dispersion if the gas bubbles were small (occupied less than 5% of the total pore volume) [73].…”
Section: Discussionmentioning
confidence: 99%
“…The bubbles have the same effect as clay particles or sand grains and effectively retard the passage of water. The forces that resist movement of the bubbles may result from at least one or more of three causes: (1) Simple blocking of the air bubbles by sand grains, (2) a phenomenon called the Jamin effect (Smith and Crane, 1930), and (3) distortion of gas bubbles when they are forced through the capillary openings (Gardescu, 1930;and Orlob and Radhakrishna, 1958). The principle of the phenomenon called the Jamin effect is that a capillary tube containing restrictions and filled with a chain of alternate air and water bubbles is capable of sustaining a finite pressure.…”
Section: Air Entrainmentmentioning
confidence: 99%